Answer:
452
Explanation:
nth term formula: An=a + (n - 1)d
An=nth term
a= 1st term
n=the term# u need to find
d= common difference
common difference in our case is 32-12=20
20 is the common
substitute this value into the nth term formula:
An=-8+(24-1)*20
An=452
Hope this helps!
You can see that two consecutive terms always differ by 20.
In other words, you generate the next term in the sequence by adding 20 to the previous one.
This implies the following structure:
In particular, this implies
6.0m questions
7.8m answers